Pemberhentian Antar Waktu Anggota KPu (Analisis Putusan Mahkamah Konstitusi No. 80/Puu-Ix/2011) - R. Nazriyah (The Constitutional Court of the Republic of Indonesia, 2016)
The formulation of article 27 paragraph (1) letter b of Law Governing the election and article 27 paragraph (3) was considered discriminatory because it prohibits members of the general election commission to resign before the end of his term. If resigned for reasons that cannot be accepted and being dishonorably are required to reimburse the honor as much as 2 (two) times the accepted. That provision was filed judicial review to the Constitutional Court. The Constitutional Court states the phrase.... with an acceptable reason’ in article 27 paragraph (1) letter b and article 27 paragraph (3) of Law No. 15 of 2011 is contrary to the Constitution and has no binding legal force. The Constitutional Court also assess interpretation ‘acceptable reason’ it has narrowed the freedom of a person to get a job and a better income in order to be better able to meet the right to life, sustaining live and life.